2017
DOI: 10.18632/oncotarget.18621
|View full text |Cite
|
Sign up to set email alerts
|

Human CAFs promote lymphangiogenesis in ovarian cancer via the Hh-VEGF-C signaling axis

Abstract: Cancer-associated fibroblasts (CAFs) play a pivotal role in the development and progression of many human cancers. Recent studies have shown that Hedgehog (Hh) signalling modulates the stromal microenvironment and prepares a suitable niche for tumour metastasis. However, the detailed molecular mechanisms underlying CAF-mediated lymphangiogenesis have not been fully elucidated. Therefore, our goal is to illustrate whether Hh ligands can activate Hh signalling in CAFs in a paracrine fashion and elucidate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Ovarian cancer cell expression HOXA9 induces CAFs to secrete CXCL12, IL-6, and VEGF-A expression, which promotes angiogenesis [ 87 ]. Ovarian cancer CAFs have also been shown to induce angiogenesis by secreting VEGF-C as a result of induction by Sonic Hedgehog (SHH) from ovarian cancer cells [ 88 ]. While angiogenesis can be induced by cancer cells as well as the tumor microenvironment, CAFs are important direct or indirect contributors to the process, and hence towards cancer progression.…”
Section: Caf Functionsmentioning
confidence: 99%
“…Ovarian cancer cell expression HOXA9 induces CAFs to secrete CXCL12, IL-6, and VEGF-A expression, which promotes angiogenesis [ 87 ]. Ovarian cancer CAFs have also been shown to induce angiogenesis by secreting VEGF-C as a result of induction by Sonic Hedgehog (SHH) from ovarian cancer cells [ 88 ]. While angiogenesis can be induced by cancer cells as well as the tumor microenvironment, CAFs are important direct or indirect contributors to the process, and hence towards cancer progression.…”
Section: Caf Functionsmentioning
confidence: 99%
“…Wei and coauthors recently demonstrated that SHH ligands increase PTCH1 and Gli1 expression leading to Hh signaling pathway activation in human CAF but not in normal fibroblasts. In the same study, Hh signaling stimulation augmented CAF proliferation and confirmed lymphangiogenesis in a xenograft model [95]. The Hh pathway also supports tumor cell invasion by stimulating cell motility and MMPs expression and by directly targeting genes implicated in EMT.…”
Section: Hh Signaling In Cancer-associated Fibroblastsmentioning
confidence: 65%
“…These changes are in accordance with the role of CAFs in tumor spread and their role in tumor stroma infi ltration and metastasis. As far as is known today, this role seems to be one of the most important for tumor agressiveness (41)(42)(43). Therefore, it seems plausible that the growth factors as well as others, still not complely understood soluble mediators produced and excreted by CAFs may have a role in both angio and lymphangiogenesis in breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%